Burkitt’s Lymphoma Related to Epstein–Barr Virus Infection During Pregnancy - Cordeiro, A (2009)
Setting: Burkitt’s lymphoma is a rare form of cancer and is an extremely rare diagnosis during pregnancy. This form of lymphoma is a very fast growing B cell neoplasm and chemotherapy is the treatment of choice for the disease in all its stages. Case report: The authors describe the case of a Caucasian 40-year-old nulliparous woman, with previous known Epstein–Barr virus infection, that presents at 28 weeks gestation with supraclavicular adenopathy and multiple bilateral breast nodules, in which biopsy showed non-Hodgkin lymphoma, Burkitt’s type. Discussion: There are few described cases of Burkitt’s lymphoma during pregnancy and in general the outcomes have been poor. In most of the cases, the patients were not treated by current standards or instead had a late diagnosis. This neoplasia is the most rapidly progressive human tumor, and any delay in initiating therapy can adversely aVect patient’s prognosis. The authors discuss treatment options in pregnancy and its perinatal implications.